Respuesta :

Answer:

5(c) - 6 = 4 - 3(c) is wrong

Step-by-step explanation:

The other problems are correct and equal. This one is wrong because when you do the equations you get 19 = -11 which is clearly not equal. You would need to change the equation to make it equal. So it would be:

5(c) - 6 = 4 - -3(c) so now it is 19 = 19.

So you would change 5(c) - 6 = 4 - 3(c)  into 5(c) - 6 = 4 - -3(c)

I hope this helps :)

Answer:

The error is the problem 5c-6=4-3c.

Step-by-step explanation:

Because, it doesn't follow the rule c=5. All the problems need to abide by c=5. So the error is 5c-6=4-3c. If you do need to change it, you just need to change the 3c in the problem into -3c.

Basically the error is that the 3c in the problem is positive not negative.

Good luck! :D